Coastal Meadow Vegetation Following a Century of Shielding Behind a Dike - Andersen, Line Holm; Knudsen, Jeppe Storgaard; Sørensen, Thomas Bo; Skærbæk, Anna Sofie Krag; Bahrndorff, Simon; Pertoldi, Cino; Trøjelsgaard, Kristian; Bruhn, Dan (Estuaries and coasts, 2021)
It is still common practice in Europe to dike salt marshes for agricultural use. This impacts both the vegetation and physical environment of the marsh. We studied the plant community, environmental conditions, and determined correlations between vegetation cover and diversity with environmental factors on an enclosed marsh, which has been behind a dike since 1890. Vegetation data from both salt marshes without dikes and fresh meadows are routinely sampled by the Danish Environmental Protection Agency and were here used to assess whether the plant community of the shielded marsh resembled that of either salt marshes or fresh meadows. The century-long elimination of tidal and storm flooding has resulted in low salinity levels (0.4–5.13 ppt), low available P (0.36–4.90 mg/100 g soil), and high total N (0.68–28.82 g/kg). The plant community of the shielded marsh demonstrated a mean species richness (11.4) similar to that of other salt marshes but was no longer characterized by the same composition of halophytes (ANOSIM, p < 0.001). However, despite the century-long shielding the vegetation does not resemble that of the nearby fresh meadow community (ANOSIM, p < 0.001). Therefore, prohibiting tidal floodings by dikes does not protect the salt marsh habitat but instead results in a habitat that contains both halophytes and glycophytes.